DEVELOPMENT OF POLITICAL SCIENCE: POLITICAL THEORIES IN THE CONTEMPORARY ERA - Loso Judijanto; Dwian Hartomi Akta Padma Eldo; Afif Syarifudin Yahya (Adisam Publisher, 2024)
The development of political science in the contemporary era is marked by various shifts and advances in viewpoints and theoretical approaches. The influence of technology, changing dynamics of public participation, and unique geographical and temporal contexts, all contribute to the complexity of applying contemporary political theory, especially in the Indonesian context. The evolution of political thought has witnessed fluctuations from the classical to the contemporary era, with a transition towards behavioral approaches in the study of politics. The shift towards a behavioral approach to politics marked a significant departure from the previous emphasis on political thought as a philosophy closely linked to the history of philosophy. In contemporary politics, there are various trends and crucial issues such as globalization, environmental issues, inequality, human rights and technological developments. In the development of political science, there are several political theories that have developed throughout the contemporary era. Here are some of them, namely political realism, liberalism, constructivism, feminism, dependency theory, and postcolonialism. The research method that will be used in this article is a qualitative method with a focus on literature study. This research discusses political theories of the contemporary era and the challenges facing contemporary politics.